Karapan Sapi: The Implementation of Madura’s Culture as an English Learning Medium - Nur Halimah (Asshika: Journal of English Language Teaching and Learning, 2023)
This article discusses the application of the Karapan Sapi culture as a medium of learning English at the primary school level. This research aims to explore the potential of using local culture as an effective means of teaching English to young students. The research method used is the development and implementation of learning programs that integrate the cultural elements of the Madura Cow Carpentry, including traditions, values, and related skills. This article provides an overview of the implementation results, their impact on students' motivation and understanding of English, as well as recommendations for further development in the context of local culture-based English teaching in primary schools. The results of this research are expected to contribute positively to the approach to learning English at the primary level through the use of local cultures as an attractive and relevant learning medium for students.